1995
DOI: 10.1074/jbc.270.25.14958
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of ER-60 Protease in the Degradation of Misfolded Proteins in the Endoplasmic Reticulum

Abstract: Wild-type human lysozyme (hLZM) is secreted when expressed in mouse L cells, whereas misfolded mutant hLZMs are retained and eventually degraded in a pre-Golgi compartment (Omura, F., Otsu, M., Yoshimori, T., Tashiro, Y., and Kikuchi, M. (1992) Eur. J. Biochem. 210, 591-599). These misfolded mutant hLZMs are associated with protein disulfide isomerase (Otsu, M., Omura, F., Yoshimori, T., and Kikuchi, M. (1994) J. Biol. Chem. 269, 6874-6877). From the observation that this degradation is sensitive to cysteine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 32 publications
2
68
1
1
Order By: Relevance
“…Recently, ER-60 protease, an ER-resident protein with cysteine protease activity (53,54), has been characterized and related to ER degradation in vivo for the first time by its association with misfolded human lysozyme prior to its degradation (52). In addition to ER-60, a second protease, termed ER-72 protease, has also been identified in the ER and is inhibited by cysteine protease inhibitors (55).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ER-60 protease, an ER-resident protein with cysteine protease activity (53,54), has been characterized and related to ER degradation in vivo for the first time by its association with misfolded human lysozyme prior to its degradation (52). In addition to ER-60, a second protease, termed ER-72 protease, has also been identified in the ER and is inhibited by cysteine protease inhibitors (55).…”
Section: Discussionmentioning
confidence: 99%
“…ERp57 exhibits a lower redox activity than PDI, as seen in a glutathione-insulin transhydrogenase assay [150,151], and cannot substitute for PDI in P4H [116]. Although ERp57 has been claimed to possess carnitine medium\long-chain acyltransferase (CPT) activity [152,153] and proteolytic activity [137,154,155] dependent on its active-site cysteines [156], both of these claims have been challenged [157].…”
Section: Molecularmentioning
confidence: 99%
“…ERp57 has thiol-dependent reductase activity (29), cysteine-dependent protease activity (30,31), and is known to interact with glycoproteins in a manner that can involve forming complexes with either CXN and CRT (32)(33)(34). Three recent reports demonstrated that ERp57 is detected in association with class I molecules before peptide binding (26 -28).…”
Section: Association Of Erp57 Withmentioning
confidence: 99%